The Emerging Role of Lamin C as an Important LMNA Isoform in Mechanophenotype - González-Cruz, Rafael D.; Dahl, Kris N.; Darling, Eric M. (Frontiers in Cell and Developmental Biology, 2018)
Lamin A and lamin C isoforms of the gene LMNA are major structural and mechanotransductive components of the nuclear lamina. Previous reports have proposed lamin A as the isoform with the most dominant contributions to cellular mechanophenotype. Recently, expression of lamin C has also been shown to strongly correlate to cellular elastic and viscoelastic properties. Nevertheless, LMNA isoforms exist as part of a network that collectively provides structural integrity to the nucleus and their expression is ultimately regulated in a cell-specific manner. Thus, they have importance in mechanotransduction and structural integrity of the nucleus as well as potential candidates for biomarkers of whole-cell mechanophenotype. Therefore, a fuller discussion of lamin isoforms as mechanophenotypic biomarkers should compare both individual and ratiometric isoform contributions towards whole-cell mechanophenotype across different cell types. In this perspective, we discuss the distinctions between the mechanophenotypic correlations of individual and ratiometric lamins A:B1, C:B1, (A+C):B1, and C:A across cells from different lineages, demonstrating that the collective contribution of ratiometric lamin (A+C):B1 isoforms exhibited the strongest correlation to whole-cell stiffness. Additionally, we highlight the potential roles of lamin isoform ratios as indicators of mechanophenotypic change in differentiation and disease to demonstrate that the contributions of individual and collective lamin isoforms can occur as both static and dynamic biomarkers of mechanophenotype.